Uji Aktivitas Antikoagulan pada Sel Darah Manusia dari Ekstrak Bawang Bombai (Allium cepa L.) - Fany Febriani; Junius Hardy; Riskianto (Pro-Life, 2023)
Thromboembolic disorders can cause various life-threatening cardiovascular diseases. Anticoagulants are the most common treatment for thromboembolic disorders. Organosulfur compounds in onions, such as allicin and flavonoid compounds, have anticoagulant properties. The purpose of this study is to test the anticoagulant activity of onions extracted by maceration method using 96% ethanol as a solvent. The anticoagulant test was performed on samples of blood groups A, B, AB, and O using the Lee-White method. Six tubes were filled with 1 cc of each blood sample with treatments including control (without treatment), negative control (96% ethanol), positive control (EDTA), and variation of extract concentrations 5; 7.5; 10%. The results of 96% ethanol extract of Onion (Allium cepa Linnaeus) using the maceration method contains secondary metabolites including flavonoids, saponins, and phenols. The onion extract had a significant mean difference (p < 0.05) with the EDTA positive control group and did not produce a significant mean difference (p > 0.05) with the untreated group, so the onion extract with a concentration of 5; 7.5; 10% extracted with 96% ethanol solvent using maceration method had no anticoagulant activity. Blood type A, B, AB, and O did not have a significant difference in the mean blood clotting time with a value of P = 0.504 (p > 0.05).